Long-Term Effects of Sharia Stock Status Changes on Returns and Liquidity - Purnomo, Dwi Tjahjo; Lestari, Rohmini Indah (Jurnal Manajemen Dayasaing, 2025)
This study examines the long-term impact of changes in Sharia stock status (CSS) on abnormal returns (AR) and liquidity (LIQ) in the Indonesian Sharia Stock Index (ISSI). The analysis explores liquidity’s mediating and moderating roles to clarify how Sharia screening outcomes shape market behavior beyond short-term announcement effects. Monthly data from 2018–2024 are analyzed using an event-study framework and Partial Least Squares Structural Equation Modelling (PLS-SEM) to test direct, indirect, and interaction effects grounded in signaling, asymmetric information, and liquidity theories. The findings show that CSS strongly affects liquidity for excluded stocks but only marginally influences liquidity for included stocks. CSS does not directly generate abnormal returns for excluded firms, while inclusion triggers short-term return pressure. Liquidity acts as a significant mediating channel, particularly following exclusion, translating compliance-related signals into price adjustments. No moderating effect is identified, indicating that liquidity operates sequentially rather than conditionally. Model diagnostics confirm strong predictive performance for liquidity and relatively weaker explanatory power for returns, highlighting other contributing market forces. This study provides novel long-horizon evidence on Sharia index dynamics and underscores liquidity’s strategic relevance for investors and regulators in strengthening Islamic capital market efficiency and compliance mechanisms.